A Case of Systemic Lupus Erythematosus with Cutaneous Leukocytoclastic Vasculitis Mimicking Bullous SLE - Fumi Miyagawa; Kohei Ogawa; Takashi Hashimoto; Hideo Asada (Karger Publishers, 2021)
Rarely, patients with systemic lupus erythematosus (SLE) develop bullous eruptions, a disease called bullous SLE in a narrow sense that has autoantibodies against type VII collagen. We describe an unusual case in which a patient with SLE developed extensive bullae on her lower extremities. Histologically, the bullous lesions were suggestive of leukocytoclastic vasculitis with deposition of C3 within blood vessel walls. Immunoblot analyses and enzyme-linked immunosorbent assays were negative for anti-type VII collagen antibodies. We initially considered bullous SLE, but eventually made a diagnosis of secondary vasculitis in SLE. The oral prednisolone dose was increased, and the vesiculobullous lesions resolved. The clinical presentations of cutaneous vasculitis in SLE include palpable purpura, petechiae, papulonodular lesions, and livedo reticularis. Bullous lesions seem to be uncommon. Physicians need to be aware that extensive bullae can occur as a result of secondary vasculitis in SLE, even if the patient does not exhibit high disease activity.